Peran Kepribadian dan Kecerdasan Emosional Pustakawan dalam Membentuk Kepuasan Pengguna - Wahyunisa; Muhammad Ridwan (Media Informasi, 2026)
Academic libraries function not only as providers of information resources but also as spaces for service interactions that shape users’ experiences and satisfaction. However, studies examining the role of librarians’ personality and emotional intelligence in influencing user satisfaction remain relatively limited, particularly within the context of academic libraries in Indonesia. This study aims to explore how librarians’ interpersonal personality traits and emotional intelligence contribute to shaping users’ service experiences at the Library of Universitas Islam Negeri Sumatera Utara. The study employed a qualitative method with a case study approach. Data were collected through observation, semi-structured interviews with two librarians and sixteen students from eight faculties, as well as a literature review. Data analysis was conducted using the interactive model of Miles and Huberman, including data reduction, data display, and thematic conclusion drawing. The findings reveal that librarians’ friendly, professional, and communicative attitudes contribute to positive service experiences for students. In addition, dimensions of emotional intelligence such as empathy, self-regulation, and social skills play a significant role in creating supportive, comfortable, and non-intimidating service interactions. Users perceive service quality not only through technical aspects but also through the emotional experiences that emerge during interactions with librarians. This study emphasizes that strengthening librarians’ emotional competencies is an essential component in improving service quality and user satisfaction in academic libraries.